The impacts of losing health insurance - Laura M. Argys; Andrew Friedson; M. Melinda Pitts; D. Sebastian Tello-Trillo (Federal Reserve Bank of Atlanta, 2017)
A main goal of health insurance is to smooth out the financial risk that comes with health shocks and health care. Nevertheless, there has been relatively sparse evidence on how health insurance affects financial outcomes. The few studies that exist focus on the effect of gaining health insurance. This paper explores the effect of losing public health insurance on measures of individual financial well-being. In 2005, the state of Tennessee dropped about 170,000 individuals from Medicaid, resulting in a plausibly exogenous shock to health insurance status. Both across- and within-county variation in the size of the disenrollment is linked with individual-level credit risk score and debt data to identify the effects. The results suggest that the disenrollment resulted in a 1.73 point decline in credit risk scores for the median individual in Tennessee. There is also evidence of increases in the amount and share of delinquent debt (90 days past due or more) and of increases in bankruptcy risk. These findings are mostly concentrated among individuals who were in relatively worse financial status before the disenrollment and suggest that there are significant negative consequences to current recipients that would need to be considered in the cost and benefit calculations around rollbacks of recent Medicaid expansions.
Keywords: D14; H75; I13; 330; Medicaid; public assistance; household finance; debt; bankruptcy